2020
DOI: 10.3390/su12062564
|View full text |Cite
|
Sign up to set email alerts
|

The Psychomotor Profile of Pupils in Early Childhood Education

Abstract: The aim of the article was to find out the psychomotor profile of children in the second cycle of infant education (3–6 years) through an observational cohort study with a prospective character. A total of 277 students participated, 52.7% boys and 47.3% girls, grouped in a control group (52.3%) and an experimental group (47.7%). The McCarthy Scales of Aptitude (MCSA) and Psychomotor Skills for Children, 7th edition, were used. The results showed that, in the global score and its dimensions, the time factor had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
6
0
7
Order By: Relevance
“…Regarding gross motor skills, some studies have found that boys outperform girls (Bolger et al, 2018(Bolger et al, , 2020Wang et al, 2020), while other studies have suggested that girls outperform boys (Matarma et al, 2020) and others have found no differences between both sexes (Peyre et al, 2019;Martínez-Moreno et al, 2020). In terms of fine motor skills, girls have been found to have better performance than boys (Kokstejn et al, 2017;Peyre et al, 2019;Mecías-Calvo et al, 2021), although other studies have suggested that fine motor skills are very similar between both sexes (Martínez-Moreno et al, 2020).…”
Section: Sexmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding gross motor skills, some studies have found that boys outperform girls (Bolger et al, 2018(Bolger et al, , 2020Wang et al, 2020), while other studies have suggested that girls outperform boys (Matarma et al, 2020) and others have found no differences between both sexes (Peyre et al, 2019;Martínez-Moreno et al, 2020). In terms of fine motor skills, girls have been found to have better performance than boys (Kokstejn et al, 2017;Peyre et al, 2019;Mecías-Calvo et al, 2021), although other studies have suggested that fine motor skills are very similar between both sexes (Martínez-Moreno et al, 2020).…”
Section: Sexmentioning
confidence: 98%
“…These differences have been primarily explained by the different stereotyped activities, sporting or other, that are carried out by the different sexes, and not by differences in their physical characteristics (body type, body composition, strength, and limb length), since, before puberty, these characteristics are quite similar in both boys and girls (Bolger et al, 2020;Matarma et al, 2020). Some studies, however, have failed to find differences in preschool motor skills between boys and girls (Martínez-Moreno et al, 2020).…”
Section: Sexmentioning
confidence: 99%
“…En cuanto a las comparaciones realizadas por sexo (tabla 4), un estudio realizado en niños españoles de 3 a 6 años revela resultados similares al no identi#carse diferencias signi#cativas en las comparaciones por sexo (Martínez-Moreno et al, 2020). Se aclara que en este estudio se determinó el per#l psicomotor mediante el test de habilidades psicomotoras para niños (séptima edición).…”
Section: Discussionunclassified
“…El concepto de psicomotricidad y su educación ha ido evolucionando a lo largo de los años desde visiones normativas y tradicionales hacia posturas más dinámicas (Berdila et al, 2019;Gamonales, 2016;Pescari y Popescu 2012;Rigal 2006;Rivas y Madrona 2003;Talaghir et al, 2019) para las que el desarrollo psicomotor está más relacionado con la dimensión afectiva, la vivencia y la experimentación. En la actualidad, la psicomotricidad educativa se basa en la psicología evolutiva y la pedagogía activa y pretende fomentar el desarrollo global en el niño (desarrollo equilibrado de lo motor, lo afectivo y lo mental) y facilitar sus relaciones con el mundo exterior otorgándole gran valor a su impulso en las etapas iniciales (Dumitru, 2018;Faria y Costa, 2016;Martínez-Moreno et al, 2020).…”
Section: Estado De La Cuestión: Formación Docente En Psicomotricidad unclassified